Common Ownership, Competition, and Top Management Incentives - Miguel Antón; Florian Ederer; Mireia Giné; Martin C. Schmalz (Center for Economic Studies and ifo Institute (CESifo), 2016)
We show theoretically and empirically that executives are paid less for their own firm's performance and more for their rivals' performance if an industry's firms are more commonly owned by the same set of investors. Higher common ownership also leads to higher unconditional total pay. We exploit quasi-exogenous variation in common ownership from a mutual fund trading scandal to support a causal interpretation. These findings challenge conventional assumptions in the corporate finance literature about the objective function of the firm.
Keywords: G30; G32; D21; J31; J41; 330; common ownership; competition; incentives; executive pay